2023
DOI: 10.1038/s41467-023-37685-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neurodegeneration biomarker concentrations associate with glymphatic and meningeal lymphatic measures in neurological disorders

Abstract: Clearance of neurotoxic brain proteins via cerebrospinal fluid (CSF) to blood has recently emerged to be crucial, and plasma biomarkers of neurodegeneration were newly introduced to predict neurological disease. This study examines in 106 individuals with neurological disorders associations between plasma biomarkers [40 and 42 amino acid-long amyloid-β (Aβ40 and Aβ42), total-tau, glial fibrillary acidic protein (GFAP), and neurofilament light (NfL)] and magnetic resonance imaging measures of CSF-mediated clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
2
9
0
Order By: Relevance
“…Plasma biomarker concentrations appear to be influenced by underlying diseases. 44 In our study, we observed that plasma NfL was significantly higher in the SCI+ group compared to the SCIgroup. Within the SCI+ group, we also found a significant nega- previous cross-sectional study, although they measured Aβ42/40 using CSF.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Plasma biomarker concentrations appear to be influenced by underlying diseases. 44 In our study, we observed that plasma NfL was significantly higher in the SCI+ group compared to the SCIgroup. Within the SCI+ group, we also found a significant nega- previous cross-sectional study, although they measured Aβ42/40 using CSF.…”
Section: Discussionsupporting
confidence: 46%
“…Plasma biomarker concentrations appear to be influenced by underlying diseases 44 . In our study, we observed that plasma NfL was significantly higher in the SCI+ group compared to the SCI‐ group.…”
Section: Discussionsupporting
confidence: 43%
“…In our study, several biomarkers were significantly decreased in Pk -infected individuals compared to healthy controls, including GFAP, BDNF, CaBD, CNTN1, NCAM-1, and KLK6. The astrocytic intermediate filament protein GFAP, used in clinical settings to assess severity of traumatic brain injury (49), glymphatic function (50), and neurodegeneration (51,52), was not found to be elevated in Ugandan children with falciparum cerebral malaria and severe malarial anemia (44). In contrast, the observed differences in GFAP levels in our groups may suggest altered astroglial and/or glymphatic functions in infected participants, supporting our hypothesis of cerebral involvement in Pk malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Although this statistically significant association was only observed in one sleep duration group (6–7 h), it remained present in the analysis using dichotomous sleep durations (>7 h versus < 7 h) [ 30 ]. However, some studies came up with different evidence: no significant correlation was found between total PSQI score and plasma biomarker concentrations, and there was no significant difference in plasma biomarker concentrations between good (PSQI total score≤5) and poor (PSQI total score > 6) sleep quality [ 31 ]. In the research of AD and RBDSQ, a previous study found that smaller pineal parenchymal volume in AD patients is associated with increased symptoms of RBD (assessed by RBDSQ) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering previous studies, there is a lack of evidence indicating peripheral Aβ peptides change in response to sleep deprivation, suggesting that measurements of peripheral Aβ biomarkers may be less accurate in reflecting changes in the central nervous system due to sleep deprivation. In another study, plasma concentrations of T-tau, GFAP, and NfL increased during the day and T-tau decreased significantly at night, suggesting the clearance during sleep, possibly through lymphatic fluid or CSF, although different changes in the said biomarkers were observed in other cohorts [ 31 ]. The above evidence suggests that certain AD biomarkers exhibit diurnal variation that may be independent of sleep, providing theoretical support to use SCI to reflect the combination of daytime and nighttime conditions.…”
Section: Discussionmentioning
confidence: 99%